Yohimbine-related Alkaloids from Tabernaemontana corymbosa - Nugroho, Alfarius Eko; Moue, Miho; Sasaki, Tadahiro; Shirota, Osamu; A. Hadi, A. Hamid; Morita, Hiroshi (SAGE Publications, 2018)
Five new yohimbine-type indole alkaloids were isolated from the leaves of Tabernaemontana corymbosa. Their structures were determined on the basis of the NMR and Circular Dichroism (CD) spectroscopy.